Industrial training report: Intellectual Property Corporation of Malaysia (MYIPO) - Syed Mohd Fadhillah, Sharifah Nurfaiqah (Faculty of Business and Management, 2023)
This executive summary provides an overview of the industrial training experience conducted at the Intellectual Property Corporation of Malaysia (MylPO) during 5 months and 15 days, which started on the 1st of March 2023 until 15th of August 2023. The purpose of the training was to gain practical exposure to the functioning and operations of MylPO as a regulatory body responsible for intellectual property rights in Malaysia. The industrial training at MylPO was undertaken as part of the academic requirements for internship (MGT666). The main objective was to bridge the gap between theoretical knowledge and real-world applications in the field of office system management and working environment. I have been assigned to work in Copyright Department in MylPO headquarters in Petaling Jaya. I had learned the general knowledge on intellectual property and the work conducted by the copyright department. Throughout the training period, I had been assisting accepting application, submitting application to the system, key in data and relevant data to the system, issuing copyright notice and certificate, and learn more on what are copyright issues and what are collective management organizations (CMO) that are working with Copyright Department in MylPO. The industrial training at MylPO proved to be an enriching experience, providing a deeper understanding of the practical aspects of intellectual property rights in copyright. The exposure to hands-on involvement in key processes have significantly contributed to personal and professional growth. Overall, the training has equipped with valuable skills and knowledge that will be beneficial in future academic pursuits and professional endeavours related to intellectual property.